Accelerator Production of Scandium Radioisotopes: Sc-43, Sc-44, and Sc-47 - Chernysheva, Margarita; Loveless, Shaun C.; Brossard, Tom; Becker, Kaelyn; Cingoranelli, Shelbie; Aluicio-Sarduy, Eduardo; Song, Jeongseong; Ellison, Paul; Nolen, Jerry; Rotsch, David A.; Lapi, Suzanne E.; Engle, Jonathan W. (Current Radiopharmaceuticals, 2021)
Scandium radioisotopes are increasingly considered viable radiolabels for targeted molecular imaging (Sc-43, Sc-44) and therapy (Sc-47). Significant technological advances have increased the quantity and quality of available radioscandium in the past decade, motivated in part by the chemical similarity of scandium to therapeutic radionuclides like Lu-177. The production and radiochemical isolation techniques applied to scandium radioisotopes are reviewed, focusing on charged particle and electron linac initiated reactions and using calcium and titanium as starting materials.
Keywords: Scandium